Impact of landmarks in urban space (Buildings) as a nucleus for organization urban space (Journal of Planner and Development, 2018)
The study deals with the study of one of the city’s vital urban elements and the spatial structure of the city and the role these elements play as influential elements in the organization of urban space. Where they dealt with general knowledge about the city’s landmarks, including its definition and classification as well as the dimensions of the landmarks, which contributed to building a general knowledge base up to the procedural definition of landmarks. The study discussed the concept of urban space and the critique of a series of previous international, Arab and local studies that dealt with the relationship and impact of the buildings in urban space for the purpose of identifying the research problem, which stated: (the need for a comprehensive knowledge framework, Both at the holistic and situational levels). The objective of the research was to: (a) Provide a comprehensive knowledge framework that illustrates the role of milestones in the organization of urban space at the holistic and local levels). In order to achieve this goal, and after the conceptual and specific framework of the role of urban space has been built, a main hypothesis has been laid down: "The landmarks of buildings affect the organization of urban space at the holistic and local levels through its holistic impact on the organization of space structure, Open space directly related to the teacher and his visual image), which in turn were divided into a set of secondary hypotheses. In order to validate the hypotheses, a practical study was initiated, a selection of research samples was selected, and the theoretical framework was applied to the selected samples, which consisted of models of global and local characteristics, in order to identify the effectiveness of the theoretical framework in the analysis of the projects, Theoretical. Where the impact of selected samples on the organization of urban space has been revealed at both the comprehensive and local levels. The impact is on the holistic level in the organization of the space structure, the organization of the optical image of the space structure, and at the local level in the organization of the space directly connected to the teacher and the organization of his visual image.